2020
DOI: 10.1111/acem.13947
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of Intravenous (IV) Acetaminophen as an Adjunct to IV Hydromorphone for Acute Severe Pain in Emergency Department Patients

Abstract: Background A fundamental challenge for emergency department (ED) clinicians is to relieve severe, acute pain while simultaneously avoiding adverse events associated with opioid analgesics. Because there is evidence that intravenous (IV) acetaminophen is an effective adjuvant analgesic in postoperative settings, we examined whether it also has a role in the ED. Methods This was a two‐arm, double‐blind randomized clinical trial. All patients received 1 mg of IV hydromorphone. Patients were then randomized to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The main findings of this study were excellent pain control using a titrated and individualized morphine analgesia in the majority of ED patients with moderate to severe pain and the absence of a difference between additional acetaminophen or placebo. These results are similar to those of previous studies that showed a lack of superiority of combining hydromorphone with acetaminophen 22,23 or combining various opioids with acetaminophen. 13 However, these studies did not take advantage of titrated and individualized opioid therapy, while an older study using the hydromorphone 1 + 1 mg titration approach showed favorable results, but 42% of all patients only needed a single dose, reflecting the inclusion of patients with less severe pain.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The main findings of this study were excellent pain control using a titrated and individualized morphine analgesia in the majority of ED patients with moderate to severe pain and the absence of a difference between additional acetaminophen or placebo. These results are similar to those of previous studies that showed a lack of superiority of combining hydromorphone with acetaminophen 22,23 or combining various opioids with acetaminophen. 13 However, these studies did not take advantage of titrated and individualized opioid therapy, while an older study using the hydromorphone 1 + 1 mg titration approach showed favorable results, but 42% of all patients only needed a single dose, reflecting the inclusion of patients with less severe pain.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, it remains unclear why acetaminophen seems to have an opioid‐sparing effect in postoperative use but not in patients presenting to the ED with moderate to severe acute pain. However, given the data on fixed‐dose opioids 13,22,23 or titrated and individualized morphine in this study (not providing evidence of differences in efficacy or side effects), it seems unlikely that acetaminophen would have an effect in ED patients. Furthermore, in ED patients with moderate to severe acute pain, initial analgesia with acetaminophen alone may delay administration of opioids and consecutive pain relief and should therefore not be considered standard treatment.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…We read with great interest the study by Bijur et al 1 that evaluated the analgesic efficacy of intravenous (IV) acetaminophen as an adjunct to IV hydromorphone for the treatment of severe, acute pain in the emergency department (ED). The study found that there was no significant difference in analgesia when 1 g of IV acetaminophen was added to 1 mg of IV hydromorphone.…”
Section: T He Editormentioning
confidence: 99%